(untitled) (International Seven Journal of Multidisciplinary, 2024)
The world has undergone several transformations throughout its existence revolutions were turning points and changed history, one of the great revolutions in the world was the so-called Industrial Revolution that brought to the world the creation of a new technology that changed the way society lived, act and think, even today in the 21st century we live with the effects of this revolution because it never stopped evolving and changing, according to some scholars we live today the so-called Industrial Revolution 4.0 with extensive studies of artificial intelligence and robotics, the use of these items has become increasingly indispensable for humans, but many of them use another technology a small "chip" called semiconductor. Semiconductor is a material used in electrical circuits and components that partially conduct electricity, is usually composed of silicon or germanium, it is present in computers, smartphones, appliances and other technological equipment. For its great importance in the world of technology the semiconductor became the target of dispute by the two world powers United States and China who seek to maintain a monopoly in the research and manufacture of these chips. This article sought to discuss the use of semiconductors in society and their relationship in the geopolitical conflict United States and China. For elaboration and development was applied the method of qualitative and descriptive research, where through literature on the subject were analyzed various aspects, political, economic and social.